Practicing ethnography : a student guide to method and methodology - Mannik, Lynda, 1957-; McGarry, Karen, 1972- (2017)
"Building on the "studying up" and "studying at home" trend in Anthropology, this methods book offers a theoretically informed guide to ethnographic methods that is also practical in approach, and reflects the challenge and concerns of contemporary ethnography. Students draw from vignettes, all situated within North America, to learn how various methods work in the real world. Practicing ethnography in a contemporary context that is familiar to students allows for them to engage in experiential learning that will not only build useful research, organizing, and writing skills, but which will also link to important theoretical concepts in anthropology and the social sciences. The book emphasizes an inductive, ethnographic approach to research. Each chapter offers an overview of a particular method, methodological issue, or research trend, followed by an extended ethnographic vignette, written explicitly for this volume, from a contemporary anthropologist about their fieldwork experiences. These highly readable vignettes showcase how ethnography informs contemporary anthropological theory, offering a unique way to discuss major concepts, methods and methodologies, and encouraging students to practice what they have learned by suggesting projects and activities they can do "at home"."-- $c Provided by publisher.
Includes bibliographical references (pages 245-255) and index.
Keywords: Ethnology $x Methodology -- Textbooks